Analyzing the Relevance of Merdeka Curriculum to 21st-Century Educational Challenges at Muhammadiyah Elementary School 14 Palembang - Aqsa, Ahmad esa Al; Fikri, Muhammad; Bela, Ibsa (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to analyze the relevance of the implementation of the Merdeka Curriculum to the challenges of 21st-century education at Muhammadiyah Elementary School 14. The background of this research lies in the need for the national education system to adapt to global changes that require students to possess higher-order thinking skills, adaptability, and strong character. The Merdeka Curriculum is expected to address these challenges through learning that focuses on competence and character development in accordance with the Pancasila Student Profile. The research utilized a descriptive qualitative method, collecting data through observations, interviews with teachers and the school principal, and document reviews. Data analysis followed the stages of reduction, display, and conclusion drawing, while source triangulation was applied to strengthen the credibility and validity of the study. The results indicate that the Merdeka Curriculum shows a high degree of relevance to the demands of 21st-century education, as it fosters independent and reflective character as well as critical thinking skills. The implementation of Project-Based Learning effectively enhances students’ collaboration, creativity, and communication skills. In addition, the integration of the Pancasila Student Profile strengthens religiosity, mutual cooperation, and global diversity values. However, the implementation of the Merdeka Curriculum still faces challenges, such as limited teacher competence and inadequate digital learning facilities. Therefore, the success of this curriculum depends on continuous support through teacher training, academic mentoring, and strengthening educational infrastructure, so that it becomes a concrete movement toward realizing holistic, contextual, and globally relevant education.